2019
DOI: 10.1080/16583655.2019.1630892
|View full text |Cite
|
Sign up to set email alerts
|

Study ofIn vitroantioxidant and DNA damage protection activity of a novel luteolin derivative isolated fromTerminalia chebula

Abstract: The present study aimed to investigate the efficacy of flavonoids isolated from the fruit of Terminalia chebula against the hydrogen peroxide-induced DNA damage. Five fractions were screened and were compared for their in vitro antioxidant activity by DPPH method and DNA protection activity by DNA nicking assay. All the extracts showed excellent antioxidant activity with IC 50 values ranging from 11.23 ± 0.18 to 36.70 ± 0.12 µg/ml. The band intensity of supercoiled, circular and linear DNA was measured in DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The antioxidant capacity of myricetin 4'-methoxy-3- O -α- l -rhamnopyranoside at a concentration of 40 μg/ml could manage oxidative damage protection by inhibiting the excess of free radicals. Our results are also in line with other authors where, K. Soumya et al reported the efficacy of flavones (luteolin) isolated from the fruit of Terminalia chebula against oxidative damage of DNA [ 33 ] and reported that the flavone significantly inhibited the formation of circular and linear forms of plasmid DNA. Even supercoiled percentage of pUC19 plasmid DNA observed for treatment with the pure compound in our study is almost higher than other standard antioxidants like catechin, luteolin, apigenin, quercetin and Kaempferol [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…The antioxidant capacity of myricetin 4'-methoxy-3- O -α- l -rhamnopyranoside at a concentration of 40 μg/ml could manage oxidative damage protection by inhibiting the excess of free radicals. Our results are also in line with other authors where, K. Soumya et al reported the efficacy of flavones (luteolin) isolated from the fruit of Terminalia chebula against oxidative damage of DNA [ 33 ] and reported that the flavone significantly inhibited the formation of circular and linear forms of plasmid DNA. Even supercoiled percentage of pUC19 plasmid DNA observed for treatment with the pure compound in our study is almost higher than other standard antioxidants like catechin, luteolin, apigenin, quercetin and Kaempferol [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“… (f) DMBA induced with Sprague Dawley and the Hesperidin corrected the gluconeogenesis, derangement with hepatic enzymes and maintained cell membrane integrity. (a) [ 68 ], (b) [ 69 ], (c) [ 70 ], (d) [ 71 ], (e) [ 72 ], (f) [ 73 ] Neohesperidin (a) MDA-MB-231 Osteosarcoma cell line Citrus fruits (Citrus lemon, Emblica officinalis) (a) Bcl2/Bax signalling pathway to apoptosis (b) ROS/JNK pathway (a) [ 74 ], (b) [ 75 ] Rutin (a) (b) MDA-MB-231 cell line (c) A549, HT 29,Caco2 Citrus fruits (Citrus lemon, Emblica officinalis) (a) Rutin-chitosan nano conjugates causes fragmentation of nuclear material in TNBC cells. (b) In-silico analysis revealed the ASK1 and JNK regulated signalling for apoptosis in MDA-MB-231 cell line (c) ROS mediated cytotoxicity (a) [ 76 ](b) [ 77 ], (c) [ 78 ] Maleic acid Targeted delivery Precision medicine Triphala Micelle formed synergistic action for drug delivery [ 79 ] Thiabendazole Breast cancer Glioblastoma cell Citrus fruits (Citrus lemon, Emblica officinalis) MCM2, MCM4-7 and MCM10 for relapse free interval and anti-angiogenesis effect (a) [ 79 ] (b) [ 41 ] Kaempferol MDA-MB-231 (b) HeLa cells (c) Streptotozin induced diabetes Triphala (a) RhoA and Rac 1 down signalling with influence to microfilament rearrangement (b) H2AX histone phosphorylation with G2/M arrest with trigger to Caspase cascade (c) GLUT 4 receptor activation with stimulation to hexokinase activity (a) [ 41 ], (b) [ 80 ](c) [ 81 ] ...…”
Section: Resultsmentioning
confidence: 99%
“…The Luteolin fraction exists in Terminalia chebula [ 69 ]and the flavonoid is found to influence the Notch signalling pathway in breast cancer cells. The effect is seen with in-corporation to micro RNAs such as MiRNA-34a, MiRNA-181a, MiRNA-139-5p, MiRNA-24, MiRNA-246 and their increased levels.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the protective effect of the extracts on DNA damage was performed using the screening of plasmid DNA pBR322 (Vivantis) treated with UV and H 2 O 2 in gel electrophoresis. Plasmid DNA's are widely used in DNA protective activity determination and give reliable results (Golla & Bhimathati, 2014;Verma, Shrivastava, & Kumar, 2015;Soumya et al, 2019). In the study, plasmid DNA samples were treated with the extracts, oxidized by H 2 O 2 + UV treatment, and then, checked on 1.25% agarose gels, according to Russo et al (2000).…”
Section: Evaluation Of the Dna Protective Effectmentioning
confidence: 99%